Sustainable Development of Wakaf In Higher Education - Anuar, Ahmad Shaifull; Bahari, Zakaria; Doktoralina, Caturida Meiwanto (Journal of Islamic Economics and Social Science (JIESS), 2023)
The development of higher education wakaf at the Higher Education Institution (IPTA) and the Private Higher Education Institute (IPTS) has been increasingly driven by the education ministry's push. The development of this higher education wakaf can also be implemented in a variety of ways based on agreements that have been discussed among the parties involved. Although the development of the wakaf of higher education is still new, it can be scrutinized to study its sustainability. Against this scenario, this paper is written with the goal of identifying sustainable development of endowment at Universiti Putra Malaysia (UPM), International Islamic University Malaysia (IIUM) and ISDEV, Universiti Sains Malaysia (USM). This study is a form of exploration and the data used is derived from a document study. Hence, the findings of this study will explain further the sustainability of the development of wakaf higher education at the institution and this information will be useful to the relevant parties especially the community who are aware of the progress of the implementation of the institution